2013
DOI: 10.1088/0004-637x/767/1/16
|View full text |Cite
|
Sign up to set email alerts
|

CORONAL ALFVÉN SPEED DETERMINATION: CONSISTENCY BETWEEN SEISMOLOGY USING AIA/SDOTRANSVERSE LOOP OSCILLATIONS AND MAGNETIC EXTRAPOLATION

Abstract: Two transversely oscillating coronal loops are investigated in detail during a flare on the 2011 September 6 using data from the Atmospheric Imaging Assembly (AIA) on board the Solar Dynamics Observatory. We compare two independent methods to determine the Alfvén speed inside these loops. Through the period of oscillation and loop length, information about the Alfvén speed inside each loop is deduced seismologically. This is compared with the Alfvén speed profiles deduced from magnetic extrapolation and spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 50 publications
6
51
2
Order By: Relevance
“…Modelling this behaviour as a fast magnetoacoustic kink mode allows the observed period of oscillation and loop length to be related to the magnetic field strength and density profile. Verwichte et al (2013) demonstrated that the results of such seismological inversions are consistent with values obtained by magnetic extrapolation and spectral observations. In addition to being a tool for remote plasma diagnostics, MHD waves might also have a significant role in the processes of coronal heating and solar wind acceleration (see e.g.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Modelling this behaviour as a fast magnetoacoustic kink mode allows the observed period of oscillation and loop length to be related to the magnetic field strength and density profile. Verwichte et al (2013) demonstrated that the results of such seismological inversions are consistent with values obtained by magnetic extrapolation and spectral observations. In addition to being a tool for remote plasma diagnostics, MHD waves might also have a significant role in the processes of coronal heating and solar wind acceleration (see e.g.…”
Section: Introductionsupporting
confidence: 87%
“…Cheung et al 2015), or information about the magnetic field from extrapolations (e.g. Verwichte et al 2013) or numerical simulations (e.g. Chen & Peter 2015), in addition to any improvements to the theoretical modelling of the relevant physical processes.…”
Section: Discussionmentioning
confidence: 99%
“…The Atmospheric Imaging Assembly (AIA) on board NASA's Solar Dynamics Observatory (SDO) satellite (Lemen et al 2012;Pesnell et al 2012) continues the stream of reported oscillation Appendices are available in electronic form at http://www.aanda.org events and further stimulates interest in these phenomena (e.g. Aschwanden & Schrijver 2011;Wang et al 2012;Gosain 2012;Verwichte et al 2013). Oscillations of this type are normally interpreted as fast kink magnetohydrodynamic (MHD) modes of cylinder-like structures (Edwin & Roberts 1983), and on this basis, procedures have been developed to deduce coronal parameters from wave properties (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, standing kink oscillations of coronal loops have been used to infer the coronal magnetic field strength (e.g. Nakariakov et al 1999;Nakariakov & Ofman 2001;White & Verwichte 2012) and it has been demonstrated that seismological inversions are consistent with values obtained by magnetic extrapolation and spectral observations (Verwichte et al 2013a). Magnetohydrodynamic waves might also have a significant role in the processes of coronal heating and solar wind acceleration (e.g.…”
Section: Introductionmentioning
confidence: 95%